The Online Jealousy Scale: an adaptation, extension, and psychometric analysis of the Facebook Jealousy Scale - Sullivan, Kieran T.; Bruchmann, Kathryn (Frontiers in Human Dynamics, 2025)
ObjectiveTo test the reliability and validity of the Online Jealousy Scale.BackgroundRomantic jealousy is often examined in online and social media settings and a validated measure of online jealousy is needed.MethodAcross two studies, the present research tests the psychometric properties of the Online Jealousy Scale (adapted from the Facebook Jealousy Scale) on an undergraduate (Study 1, N = 111) and two broader community (Study 2, N = 200; Study 3, N = 143) samples.ResultsData across all studies provide evidence of strong inter-item and test–retest reliability; and construct, convergent and discriminant validity. Consistent with other jealousy measures, evidence of three factors emerged: emotional, cognitive, and behavioral jealousy.DiscussionThese studies indicate that the OJS is a reliable and valid instrument.ImplicationsThis measure fills the need for a valid, reliable assessment of online jealousy and can be used in research about online jealousy across age and relationship type. It may also be useful for individual or couple therapy.